2008
DOI: 10.1161/strokeaha.108.516112
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microbleeds and Global Cognitive Function in Adults Without Neurological Disorder

Abstract: Background and Purpose-Increasing attention has been paid to associations between cognitive dysfunction and brain microbleeds (MBs). Because all previous studies have investigated patients with neurological disorders, we examined subjects without neurological disorder in order to clarify pathogenic relationships. Methods-A total of 518 consecutive adults without neurological disorder who had undergone health-screening tests of the brain were studied prospectively. Gradient-echo T2*-weighted MRI using a 1.5-T s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 48 publications
(42 reference statements)
5
91
3
1
Order By: Relevance
“…However, links between CMBs and cognitive function have been inconsistent, probably because of the great variability in populations, MRI techniques, and cognitive rating instruments used. 4,5,7,8,[20][21][22][23] Nevertheless, consistent with our findings, a large recent study in community-based elderly subjects showed that CMBs were independently associated with lower scores in processing speed and executive functions. 20 Another study in a large European population-based cohort 22 reported robust associations between strictly lobar CMBs and cognitive function (information processing speed and motor speed), but only weak associations for deep or infratentorial CMBs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, links between CMBs and cognitive function have been inconsistent, probably because of the great variability in populations, MRI techniques, and cognitive rating instruments used. 4,5,7,8,[20][21][22][23] Nevertheless, consistent with our findings, a large recent study in community-based elderly subjects showed that CMBs were independently associated with lower scores in processing speed and executive functions. 20 Another study in a large European population-based cohort 22 reported robust associations between strictly lobar CMBs and cognitive function (information processing speed and motor speed), but only weak associations for deep or infratentorial CMBs.…”
Section: Discussionsupporting
confidence: 90%
“…3 Recent evidence suggests that CMBs are linked to cognitive impairment 4,5 particularly executive function or processing speed. [6][7][8] There is indirect evidence that CMB location reflects the underlying small vessel disease process (strictly lobar CMBs being a marker for CAA; deep CMBs for hypertensive arteriopathy), 9 but the importance of CMB location with regard to cognition remains uncertain.…”
mentioning
confidence: 99%
“…The same system of health screening tests of the brain was described in previous studies. 14,15 These individuals were considered potential study subjects. To be included, subjects had to meet the following criteria: (1) age X30 years; (2) no disability in instrumental activities of daily living; (3) ability to independently attend visits for health screening tests of the brain; and (4) voluntary provision of written, informed consent.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…CMBs have also been observed in elderly patients without known underlying pathology [13,14], as well as in other degenerative central nervous system conditions, including cerebral amyloid angiopathy (CAA) associated with Alzheimer's disease and vascular cognitive impairment [11], where they have been linked to cognitive dysfunction [15][16][17][18]. Thus, quantification of CMB characteristics may serve as a valuable metric for radiation-induced vasculopathy and resultant cognitive decline.…”
Section: Introductionmentioning
confidence: 99%